Pentingnya Pemahaman Bahasa Tubuh Bagi Para Guru Pendidikan Anak Usia Dini - Putu Eka Sastrika Ayu (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
As an educator in today's work, the teacher's job is to provide mentoring, guidance and assistance as well as training to students covering a vast task of transforming knowledge, as well as exercising skills that fit Their profession needs. In this context, the teacher is not expected to convey a lot of information verbally. Teachers need to use body language or non-verbal communication as a means of providing motivation and support to students during the learning process. Body language can always reveal something, than you want to convey, until it is covered though. Feelings of accepting, rejecting, being attracted, bored, hate, can all be revealed through gestures and cues secreted by body language. By understanding the meaning of body language, the teacher is able to increase confidence, improve the relationship with the children. Likewise, in the students, when the language of his body is able to understand by the teacher, he will feel cared for, dear and feel the support from his teacher